Bacterial colonization of a power‐driven water flosser during regular use. A proof‐of‐principle study - Kristina Bertl; Pia Edlund Johansson; Corinna Bruckmann; Matthias Leonhard; Julia R. Davies; Andreas Stavropoulos (Wiley, 2021)
Abstract Objectives The present proof‐of‐principle study assessed whether daily use of a power‐driven water flosser (Sonicare AirFloss; SAF) leads to bacterial colonization in the nozzle and/or the device, resulting in contaminated water‐jet. Material and Methods In five participants, saliva samples at baseline and water‐jet samples of devices used daily with bottled water for 3 weeks (test) were collected. Additionally, water‐jet samples from devices used daily with bottled water extra‐orally for 3 weeks (positive control) and from brand new devices (negative control), as well as samples from newly opened and 1‐ and 3‐week opened water bottles were collected. Colony forming units (CFU) were recorded after 48 h culturing and 20 oral pathogens were assessed by polymerase chain reaction‐based analysis. Results Distinct inter‐individual differences regarding the number of detected bacteria were observed; water‐jet samples of test devices included both aerobic and anaerobic bacterial species, with some similarities to the saliva sample of the user. Water‐jet samples from positive control devices showed limited number of aerobic and anaerobic bacterial species, while the samples from negative control devices did not show any bacterial species. Very few aerobic bacteria were detected only in the 3‐week‐old bottled water samples, while samples of newly and 1‐week opened water bottles did not show any bacterial growth. Conclusions The present proof‐of‐principle study showed that daily use of a power‐driven water flosser for 3 weeks resulted in bacterial colonization in the nozzle and/or device with both aerobic and anaerobic, not only oral, species, that are transmitted via the water‐jet.